Preparation method of zinc aluminate graphene composite material and preparation method of lead-acid battery negative electrode
By preparing zinc aluminate graphene composite materials, using zinc aluminate powder and graphene oxide to form covalent bonds in an alkaline environment, the problem of low cycling stability of existing spinel oxide materials in lead-acid batteries is solved, and higher battery capacity and cycling stability are achieved.
Patent Information
- Application Number
- CN202211724860.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-30
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-12-30
AI Technical Summary
Although existing spinel oxide materials can improve battery capacity in lead-acid batteries, their cycle stability is low, making it difficult to take into account the improvement of battery capacity and cycle performance.
By preparing zinc aluminate graphene composite material, zinc aluminate powder and graphene oxide form covalent bonds under an alkaline environment of pH 8.0-9.0, uniform dispersion of zinc aluminate is achieved and the stability of the material is improved.
The better cycle stability and battery capacity improvement of zinc aluminate graphene composite material on the negative electrode of lead-acid battery are achieved.
Smart Images

Figure CN115863619B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of batteries, and in particular to a method for preparing a zinc aluminate-graphene composite material and a method for preparing a negative electrode of a lead-acid battery. Background Art
[0002] Lead-acid battery is one of the most mature energy storage batteries currently, and the improvement of its process and battery materials is the focus of current battery research. Graphene material is a two-dimensional layered material. The composite of graphene material and lead-acid battery positive and negative electrode materials can improve the battery's cycle stability and battery capacity, which is due to the good mechanical properties and dual capacitance effect of graphene material. In addition to graphene carbon materials, materials that can produce capacitance effect include metal oxide materials and conductive polymer materials. Among them, metal oxide materials realize energy storage through the Faraday pseudocapacitor generated by the redox reaction of metal ions. Spinel oxides such as cobaltates, manganates, and nickelates are a class of compounds with good capacitance performance. At the same time, spinel materials also have the advantages of abundant raw materials and low preparation cost. However, the lattice structure of spinel oxide materials changes greatly during the redox reversible transformation process. When used in lead-acid batteries, although the capacity of the battery can be increased, the cycle stability will be significantly reduced. Therefore, the existing spinel oxides are used in lead-acid batteries, which cannot take into account the improvement of battery capacity and cycle performance. Summary of the invention
[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a zinc aluminate-graphene composite material and a method for preparing a lead-acid battery negative electrode, which can improve battery capacity and have good cycle stability.
[0004] The objective of the present invention is achieved through the following technical solutions:
[0005] A method for preparing a zinc aluminate-graphene composite material comprises the following steps:
[0006] preparing zinc aluminate powder;
[0007] preparing zinc aluminate graphene composite materials;
[0008] The specific steps of preparing the zinc aluminate graphene composite material are as follows:
[0009] The zinc aluminate powder, graphene oxide powder and anhydrous ethanol are prepared into a mixed powder;
[0010] Adding the mixed powder into deionized water to obtain a mixed solution;
[0011] Adjusting the pH of the mixed solution so that the pH of the mixed solution is between 8.0 and 9.0;
[0012] performing ultrasonic operation on the mixed solution;
[0013] Performing a homogenizing operation on the mixed solution after ultrasound;
[0014] Performing a vacuum drying operation on the mixed solution after the homogenization operation to obtain the zinc aluminate-graphene composite material;
[0015] Wherein, after the mixed solution is in an alkaline environment of pH 8.0-9.0, the carboxyl functional groups, hydroxyl functional groups and carbonyl functional groups on the surface of the graphene oxide are activated, and the carboxyl functional groups, hydroxyl functional groups and carbonyl functional groups on the surface of the graphene oxide are all activated with the [AlO3] 2- The zinc aluminate and the graphene oxide are combined to form a covalent bond and then are evenly dispersed in the graphene oxide.
[0016] In one embodiment, the specific steps of preparing zinc aluminate powder are as follows:
[0017] dissolving a soluble aluminum salt and a soluble zinc salt in the anhydrous ethanol to obtain a mixed salt solution;
[0018] Adding polyethylene glycol to the mixed salt solution and performing heating and stirring operations to obtain a mixed gel solution;
[0019] The mixed gel solution is sintered to obtain the zinc aluminate powder.
[0020] In one embodiment, the soluble aluminum salt is one or both of aluminum nitrate and aluminum chloride.
[0021] In one embodiment, the soluble zinc salt is at least one of zinc nitrate, zinc acetate, zinc chloride, zinc bromide, and zinc propionate.
[0022] In one embodiment, the sintering operation temperature is 500°C-900°C.
[0023] In one embodiment, the sintering operation time is 5h-8h.
[0024] In one embodiment, the pressure of the homogenization operation is 20MPa-40MPa.
[0025] In one embodiment, the homogenization operation time is 30min-60min.
[0026] In one embodiment, the vacuum drying temperature is 120°C-160°C.
[0027] A lead-acid battery negative electrode comprises the following steps:
[0028] Providing the zinc aluminate-graphene composite material prepared by the preparation method of the zinc aluminate-graphene composite material described in any one of the above embodiments;
[0029] The zinc aluminate graphene composite material, lead powder, sulfuric acid and water are mixed into a paste-like mixed slurry;
[0030] The paste-like mixed slurry is coated on a negative electrode alloy grid to obtain the lead-acid battery negative electrode.
[0031] Compared with the prior art, the present invention has at least the following advantages:
[0032] The preparation method of the zinc aluminate graphene composite material of the present application first prepares zinc aluminate powder. Zinc aluminate is a type of aluminate spinel oxide. When spinel oxide is used in the negative electrode of a lead-acid battery, it can increase the capacity of the battery. Secondly, zinc aluminate spinel, as an inorganic material, is difficult to be evenly dispersed in graphene oxide without adding a coupling agent. However, in an alkaline environment of pH 8.0-9.0, the reaction activity of the carboxyl functional group, hydroxyl functional group and carbonyl functional group on the surface of graphene oxide is effectively enhanced. Zinc aluminate is reacted with [AlO3] 2- The negatively charged groups establish a covalent bond with the surface of graphene oxide with a strong connection, so that zinc aluminate is evenly dispersed in the graphene oxide, so that the zinc aluminate graphene composite material has better stability in electrode material applications. Therefore, the zinc aluminate graphene composite material has better cycle stability when used in the negative electrode of lead-acid batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0034] Figure 1 The figure is a schematic diagram of a process for preparing a zinc aluminate graphene composite material according to an embodiment;
[0035] Figure 2 for Figure 1 A schematic flow chart of some steps of a method for preparing a zinc aluminate graphene composite material;
[0036] Figure 3 for Figure 1 A schematic flow chart of some steps of a method for preparing a zinc aluminate graphene composite material;
[0037] Figure 4is the SEM image of zinc aluminate graphene composite material;
[0038] Figure 5 TEM image of zinc aluminate graphene composite material;
[0039] Figure 6 This is the infrared spectrum of graphene oxide raw material and zinc aluminate graphene oxide composite powder. DETAILED DESCRIPTION
[0040] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.
[0041] It should be noted that when an element is referred to as being "fixed to" another element, it may be directly on the other element or there may be a central element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "left", "right" and similar expressions used herein are for illustrative purposes only and do not represent the only implementation method.
[0042] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0043] The present application provides a method for preparing a zinc aluminate graphene composite material, and the method for preparing the zinc aluminate graphene composite material comprises the following steps: preparing zinc aluminate powder; preparing a zinc aluminate graphene composite material; the specific steps of preparing the zinc aluminate graphene composite material are as follows: preparing the zinc aluminate powder, graphene oxide powder and anhydrous ethanol into a mixed powder; adding the mixed powder into deionized water to obtain a mixed solution; performing a pH adjustment operation on the mixed solution so that the pH of the mixed solution is between 8.0 and 9.0; performing an ultrasonic operation on the mixed solution; performing a homogenization operation on the mixed solution after the ultrasonication; performing a vacuum drying operation on the mixed solution after the homogenization operation to obtain the zinc aluminate graphene composite material; wherein, after the carboxyl functional groups, hydroxyl functional groups and carbonyl functional groups on the surface of the graphene oxide are activated in an alkaline environment of pH 8.0-9.0, the carboxyl functional groups, hydroxyl functional groups and carbonyl functional groups on the surface of the graphene oxide are all in contact with the [AlO3] of the zinc aluminate. 2- The zinc aluminate and the graphene oxide are combined to form a covalent bond and then are evenly dispersed in the graphene oxide.
[0044] The above-mentioned method for preparing the zinc aluminate graphene composite material first prepares zinc aluminate powder. Zinc aluminate is a type of aluminate spinel oxide. When spinel oxide is used in the negative electrode of a lead-acid battery, it can increase the capacity of the battery. Secondly, zinc aluminate spinel, as an inorganic material, is difficult to be evenly dispersed in graphene oxide without adding a coupling agent. However, in an alkaline environment of pH 8.0-9.0, the reaction activity of the carboxyl functional group, hydroxyl functional group and carbonyl functional group on the surface of graphene oxide is effectively enhanced. Zinc aluminate is reacted with [AlO3] 2- The negatively charged groups establish a covalent bond with the surface of graphene oxide with a strong connection, so that zinc aluminate is evenly dispersed in the graphene oxide, so that the zinc aluminate graphene composite material has better stability in electrode material applications. Therefore, the zinc aluminate graphene composite material has better cycle stability when used in the negative electrode of lead-acid batteries.
[0045] See also Figure 1 , Figure 3 ,and Figure 6 In order to better understand the preparation method of the zinc aluminate graphene composite material of the present application, the preparation method of the zinc aluminate graphene composite material is further explained below:
[0046] A method for preparing a zinc aluminate-graphene composite material according to an embodiment of the present invention comprises the following steps:
[0047] S100, preparing zinc aluminate powder.
[0048] In this embodiment, aluminate is one of the compounds in spinel oxide that can effectively improve the capacitance performance, and zinc aluminate is selected as the main material for improving the capacitance performance, so that the zinc aluminate graphene composite material can effectively improve the battery capacity of the lead-acid battery when applied to the negative electrode of the lead-acid battery.
[0049] S200, preparation of zinc aluminate graphene composite material.
[0050] The specific steps of preparing the zinc aluminate graphene composite material are as follows:
[0051] S201, preparing the zinc aluminate powder, graphene oxide powder and anhydrous ethanol into a mixed powder.
[0052] In this embodiment, zinc aluminate powder and graphene oxide powder are poured into a mortar, anhydrous ethanol is added to wet them, and a mixed powder is obtained after grinding for 30 minutes. That is, the zinc aluminate powder and the graphene oxide powder are better mixed together under the wetting of anhydrous ethanol.
[0053] S202, adding the mixed powder into deionized water to obtain a mixed solution.
[0054] In this embodiment, deionized water is used as a solvent, and the mixed powder is dissolved in deionized water to form a mixed solution, at which the mass fraction of the powder is 0.5-2%.
[0055] S203, performing a pH adjustment operation on the mixed solution to adjust the pH of the mixed solution to be between 8.0 and 9.0.
[0056] In this embodiment, the pH of the mixed solution is adjusted by ammonia water so that the pH of the mixed solution is between 8.0 and 9.0. Since graphene oxide is a two-dimensional layered material, zinc aluminate and the surface of graphene oxide at this time establish a covalent bond with a strong connection, so that zinc aluminate can be evenly dispersed in the graphene oxide, so that the zinc aluminate-graphene composite material has better cycle stability when used in the negative electrode of a lead-acid battery.
[0057] Furthermore, in order to ensure sufficient contact between zinc aluminate and graphene oxide, the mass ratio of zinc aluminate powder to graphene oxide powder is 1:(1.5-3). That is, there is enough graphene oxide to contact zinc aluminate to ensure sufficient contact between zinc aluminate and graphene oxide, thereby effectively improving the composite effect of zinc aluminate and graphene oxide, and then making zinc aluminate evenly dispersed in graphene oxide, further improving the battery capacity and cycle stability of zinc aluminate graphene composite materials when used in lead-acid batteries.
[0058] S204, performing ultrasonic operation on the mixed solution.
[0059] In this embodiment, by ultrasonically oscillating the mixed solution for 30 minutes, zinc aluminate can be dispersed more evenly in graphene oxide, so that the battery cycle stability of the zinc aluminate graphene composite material when applied to the negative electrode of a lead-acid battery is effectively improved.
[0060] S205, homogenizing the mixed solution after ultrasonication.
[0061] In this embodiment, the mixed liquid after ultrasound is placed in a homogenizer for homogenization. The homogenization operation allows zinc aluminate and graphene oxide in the mixed liquid to be fully contacted, so that zinc aluminate is evenly dispersed in the graphene oxide, thereby effectively improving the composite effect of zinc aluminate and graphene oxide, and further effectively improving the stability of the zinc aluminate-graphene composite material.
[0062] Furthermore, the mixed solution after the homogenization operation is centrifuged at a speed of 10000 rpm. Under the action of high-speed centrifugation, the composite effect of zinc aluminate and graphene oxide is better, that is, zinc aluminate is more evenly dispersed in graphene oxide, so that the battery cycle stability of the zinc aluminate graphene composite material when applied to the negative electrode of the lead-acid battery is further improved.
[0063] S206, performing a vacuum drying operation on the mixed solution after the homogenization operation to obtain the zinc aluminate graphene composite material.
[0064] In this example, the mixed solution is dried by a vacuum dryer to obtain the zinc aluminate graphene composite material.
[0065] Wherein, after the mixed solution is in an alkaline environment of pH 8.0-9.0, the carboxyl functional groups, hydroxyl functional groups and carbonyl functional groups on the surface of the graphene oxide are activated, and the carboxyl functional groups, hydroxyl functional groups and carbonyl functional groups on the surface of the graphene oxide are all activated with the [AlO3] 2- The zinc aluminate and the graphene oxide are combined with each other to form a covalent bond and then dispersed evenly in the graphene oxide.
[0066] It should be noted that zinc aluminate spinel is an inorganic material and graphene oxide is a two-dimensional layered material. It is difficult to disperse them evenly in graphene oxide without adding a coupling agent. However, in an alkaline environment of pH 8.0-9.0, the reaction activity of the functional groups on the surface of graphene oxide is enhanced. Zinc aluminate spinel can be dispersed in graphene oxide through [AlO3] 2- The groups establish a covalent bond with the surface of graphene oxide with a strong connection effect, and zinc aluminate is evenly dispersed in graphene oxide, so that the zinc aluminate graphene composite material has better stability in electrode material applications, and thus the zinc aluminate graphene composite material has better battery cycle stability when used in the negative electrode of lead-acid batteries.
[0067] Furthermore, if Figure 6 As shown in the figure, compared with the graphene oxide material, the zinc aluminate graphene composite powder has a wave number of 3407 cm -1 The hydroxyl vibration peak and wave number are 1727cm -1 The carbonyl vibration peak with a wave number of 1622 cm -1 The vibration intensity of the carboxyl vibration peak is significantly weakened, which means that the carboxyl functional group, hydroxyl functional group and carbonyl functional group are replaced by zinc aluminate during the composite process of graphene oxide and zinc aluminate, so that zinc aluminate is evenly and stably composited in graphene oxide.
[0068] Furthermore, if Figure 4 and Figure 5 As shown, in one embodiment, the zinc aluminate graphene composite material is subjected to scanning electron microscopy analysis and transmission electron microscopy analysis. It can be seen from the scanning electron microscopy and transmission electron microscopy images that zinc aluminate is dispersed in graphene oxide, so that the zinc aluminate graphene composite material has the ability to improve battery capacity and battery cycle performance, that is, the zinc aluminate graphene composite material has good battery capacity and cycle performance when applied to the negative electrode of a lead-acid battery.
[0069] like Figure 2 As shown, in one embodiment, the specific steps of preparing zinc aluminate powder are as follows:
[0070] S101, dissolving a soluble aluminum salt and a soluble zinc salt in the anhydrous ethanol to obtain a mixed salt solution.
[0071] In this embodiment, anhydrous ethanol is used as a solvent, and a soluble aluminum salt and a soluble zinc salt are fully dissolved in the anhydrous ethanol to obtain a mixed salt solution, wherein the content ratio of aluminum element to zinc element is 2:1.
[0072] S102, adding polyethylene glycol to the mixed salt solution and performing heating and stirring operations to obtain a mixed gel solution.
[0073] In this embodiment, polyethylene glycol plays a flocculation role in the system, so that zinc aluminate becomes gel-like, that is, after adding polyethylene glycol accounting for 2-5% of the total mass of the mixed salt solution into the mixed salt solution and stirring at high speed for 2-6 hours, the temperature is raised to 80°C and stirring is continued until the solution becomes gel-like to obtain a mixed gel solution.
[0074] S103, sintering the mixed gel solution to obtain the zinc aluminate powder.
[0075] In this embodiment, the mixed gel solution is first dried and ground, and then placed in a muffle furnace for sintering to obtain zinc aluminate powder.
[0076] Furthermore, zinc aluminate spinel is a cubic crystal composed of alternating aluminum oxide octahedra and zinc tetrahedrons. The positive divalent zinc ions at the center of the tetrahedron in the crystal are easily lost to form negatively charged zinc vacancies, so that when the zinc aluminate graphene composite material is applied to the negative electrode of a lead-acid battery, it is beneficial to accumulate negative charges and increase the overall capacity of the battery. At the same time, the zinc aluminate spinel crystal does not deform during the charge accumulation and release process, and can support and protect the negative electrode of the lead-acid battery, which is beneficial to improving the cycle stability of the negative electrode material.
[0077] In one embodiment, the soluble aluminum salt is one or both of aluminum nitrate and aluminum chloride. It should be noted that both aluminum nitrate and aluminum chloride can provide aluminum ions for the preparation of zinc aluminate.
[0078] In one embodiment, the soluble zinc salt is at least one of zinc nitrate, zinc acetate, zinc chloride, zinc bromide and zinc propionate. It should be noted that zinc nitrate, zinc acetate, zinc chloride, zinc bromide and zinc propionate can all provide zinc ions for the preparation of zinc aluminate.
[0079] In one embodiment, the sintering operation temperature is 500° C.-900° C. It should be noted that at 500-900° C., the zinc aluminate graphene composite material has a better sintering molding effect.
[0080] In one embodiment, the sintering operation time is 5h-8h. It should be noted that when the sintering time is 5h-8h, the zinc aluminate graphene composite material is sintered more fully and has a better molding effect.
[0081] In one embodiment, the pressure of the homogenization operation is 20MPa-40MPa. It should be noted that under the homogenization condition of 20MPa-40MPa, the binding property of zinc aluminate and graphene oxide in the mixed solution in the homogenization operation is effectively enhanced, that is, zinc aluminate is dispersed more evenly in graphene oxide, so that the stability of the zinc aluminate graphene composite material in the application of electrode materials is further improved, and then the battery cycle stability of the zinc aluminate graphene composite material when applied to the negative electrode of lead-acid batteries is further improved.
[0082] In one embodiment, the homogenization operation time is 30 min-60 min. It should be noted that under the condition of 30 min-60 min of homogenization operation, zinc aluminate and graphene oxide can be fully fused, that is, zinc aluminate and graphene oxide are fully contacted, and at this time, the composite effect of zinc aluminate and graphene oxide is better.
[0083] In one embodiment, the vacuum drying temperature is 120° C.-160° C. It should be noted that the drying effect of the zinc aluminate graphene composite material at 120° C.-160° C. is better.
[0084] The present application also provides a lead-acid battery negative electrode, comprising the following steps:
[0085] Providing the zinc aluminate-graphene composite material prepared by the preparation method of the zinc aluminate-graphene composite material described in any one of the above embodiments;
[0086] The zinc aluminate graphene composite material, lead powder, sulfuric acid and water are mixed into a paste-like mixed slurry;
[0087] Applying the paste-like mixed slurry on the negative electrode alloy grid to obtain the negative electrode of the lead-acid battery;
[0088] The preparation method of the zinc aluminate graphene composite material specifically comprises the following steps:
[0089] preparing zinc aluminate powder;
[0090] preparing zinc aluminate graphene composite materials;
[0091] The specific steps of preparing the zinc aluminate graphene composite material are as follows:
[0092] The zinc aluminate powder, graphene oxide powder and anhydrous ethanol are prepared into a mixed powder;
[0093] Adding the mixed powder into deionized water to obtain a mixed solution;
[0094] Adjusting the pH of the mixed solution so that the pH of the mixed solution is between 8.0 and 9.0;
[0095] performing ultrasonic operation on the mixed solution;
[0096] Performing a homogenizing operation on the mixed solution after ultrasound;
[0097] Performing a vacuum drying operation on the mixed solution after the homogenization operation to obtain the zinc aluminate-graphene composite material;
[0098] Wherein, after the mixed solution is in an alkaline environment of pH 8.0-9.0, the carboxyl functional groups, hydroxyl functional groups and carbonyl functional groups on the surface of the graphene oxide are activated, and the carboxyl functional groups, hydroxyl functional groups and carbonyl functional groups on the surface of the graphene oxide are all activated with the [AlO3] 2- The zinc aluminate and the graphene oxide are combined to form a covalent bond and then are evenly dispersed in the graphene oxide.
[0099] In this embodiment, the zinc aluminate graphene composite material with good stability is used as one of the components of the coating material, which can effectively improve the cycle stability of the lead-acid battery. At the same time, the zinc aluminate graphene composite material uses zinc aluminate spinel as a main component. The spinel oxide can increase the capacity of the battery when used in the lead-acid battery. Therefore, the capacity and cycle stability of the battery are improved when the zinc aluminate graphene composite material is used in the negative electrode of the lead-acid battery.
[0100] In another embodiment, the preparation method of the zinc aluminate graphene composite material comprises the following steps:
[0101] preparing zinc aluminate powder;
[0102] preparing zinc aluminate graphene composite materials;
[0103] The specific steps of preparing the zinc aluminate graphene composite material are as follows:
[0104] The zinc aluminate powder, graphene oxide powder, graphene powder and anhydrous ethanol are prepared into a mixed powder;
[0105] Adding the mixed powder into deionized water to obtain a mixed solution;
[0106] Adjusting the pH of the mixed solution so that the pH of the mixed solution is between 8.0 and 9.0;
[0107] performing ultrasonic operation on the mixed solution;
[0108] Performing a homogenizing operation on the mixed solution after ultrasound;
[0109] Performing a vacuum drying operation on the mixed solution after the homogenization operation to obtain the zinc aluminate-graphene composite material;
[0110] Wherein, after the mixed solution is in an alkaline environment of pH 8.0-9.0, the carboxyl functional groups, hydroxyl functional groups and carbonyl functional groups on the surface of the graphene oxide are activated, and the carboxyl functional groups, hydroxyl functional groups and carbonyl functional groups on the surface of the graphene oxide are all activated with the [AlO3] 2- The zinc aluminate and the graphene oxide are combined to form a covalent bond and then are evenly dispersed in the graphene oxide.
[0111] Since the conductivity of graphene oxide is inferior to that of graphene, but the functional groups such as carboxyl, hydroxyl and carbonyl on the surface of graphene oxide can not only adsorb zinc aluminate spinel well, but also graphene forms π-π adsorption with graphene oxide through functional groups such as carboxyl, hydroxyl and carbonyl, thereby improving the conductivity of graphene oxide. Specifically, the sheet diameter of graphene oxide in the mixed solution is 500nm to 900nm, while the sheet diameter of graphene is less than 200nm, so the conductive functional modifier of graphene with a smaller sheet diameter can be adsorbed on the graphene oxide with a larger sheet diameter. In this way, the conductivity of the obtained zinc aluminate graphene composite material is further improved, so that the battery capacity of the zinc aluminate graphene composite material when applied to lead-acid batteries is further improved.
[0112] Examples are listed below, but it should be noted that the following examples do not exhaust all possible situations, and the materials used in the following examples can be obtained from commercial channels unless otherwise specified.
[0113] Example 1
[0114] Soluble aluminum salt and soluble zinc salt are mixed according to the content ratio of aluminum element to zinc element of 2:1, and dissolved in anhydrous ethanol to obtain a mixed salt solution, 2% polyethylene glycol of the total mass of the mixed salt solution is added, and stirred at high speed for 2 hours, and the temperature is raised to 80°C and stirred until the solution becomes a gel to obtain a mixed gel solution, and the mixed gel solution is dried and ground and placed in a muffle furnace for sintering at 500°C for 8h to obtain zinc aluminate powder. Zinc aluminate powder and graphene oxide powder are mixed according to a mass ratio of 1:1.5, and then anhydrous ethanol is added to wet and grind for 30 minutes to obtain a mixture, and the mixed powder is added to deionized water to obtain a mixed solution, and ammonia water is added to adjust the pH of the mixed solution to 8.0, and the mixed solution is ultrasonically oscillated for 30 minutes, and then homogenized by a homogenizer at a pressure of 20MPa for 30 minutes, and after the homogenization operation, it is centrifuged at a speed of 10000rpm and washed twice with deionized water, and finally vacuum dried at 120°C to obtain a zinc aluminate graphene composite material.
[0115] Example 2
[0116] Soluble aluminum salt and soluble zinc salt are mixed according to the content ratio of aluminum element to zinc element of 2:1, and dissolved in anhydrous ethanol to obtain a mixed salt solution, 2% polyethylene glycol of the total mass of the mixed salt solution is added, and stirred at high speed for 4 hours, and the temperature is raised to 80°C and stirred until the solution becomes a gel to obtain a mixed gel solution, and the mixed gel solution is dried and ground and placed in a muffle furnace for sintering at 700°C for 6 hours to obtain zinc aluminate powder. Zinc aluminate powder and graphene oxide powder are mixed according to a mass ratio of 1:1.5, and then anhydrous ethanol is added to wet and grind for 30 minutes to obtain a mixture, and the mixed powder is added to deionized water to obtain a mixed solution, and ammonia water is added to adjust the pH of the mixed solution to 8.5, and the mixed solution is ultrasonically oscillated for 30 minutes, and then homogenized by a homogenizer at a pressure of 30MPa for 45 minutes, and after the homogenization operation, it is centrifuged at a speed of 10000rpm and washed with deionized water for 3 times, and finally vacuum dried at 140°C to obtain a zinc aluminate graphene composite material.
[0117] Example 3
[0118] Soluble aluminum salt and soluble zinc salt are mixed according to the content ratio of aluminum element to zinc element of 2:1, and dissolved in anhydrous ethanol to obtain a mixed salt solution, 2% polyethylene glycol of the total mass of the mixed salt solution is added, and stirred at high speed for 6 hours, and the temperature is raised to 80°C and stirred until the solution becomes a gel to obtain a mixed gel solution, and the mixed gel solution is dried and ground and placed in a muffle furnace for sintering at 900°C for 5 hours to obtain zinc aluminate powder. Zinc aluminate powder and graphene oxide powder are mixed according to a mass ratio of 1:1.5, and then anhydrous ethanol is added to wet and grind for 30 minutes to obtain a mixture, and the mixed powder is added to deionized water to obtain a mixed solution, and ammonia water is added to adjust the pH of the mixed solution to 9.0, and the mixed solution is ultrasonically oscillated for 30 minutes, and then homogenized by a homogenizer at a pressure of 40MPa for 60 minutes, and after the homogenization operation, it is centrifuged at a speed of 10000rpm and washed with deionized water for 3 times, and finally vacuum dried at 160°C to obtain a zinc aluminate graphene composite material.
[0119] Comparative Example 1
[0120] Soluble aluminum salt and soluble zinc salt are mixed according to the content ratio of aluminum element to zinc element of 2:1, and dissolved in anhydrous ethanol to obtain a mixed salt solution, 2% polyethylene glycol of the total mass of the mixed salt solution is added, and stirred at high speed for 2 hours, and the temperature is raised to 80°C and stirred until the solution becomes a gel to obtain a mixed gel solution, and the mixed gel solution is dried and ground and placed in a muffle furnace for sintering at 500°C for 8 hours to obtain zinc aluminate powder. Zinc aluminate powder and graphene oxide powder are mixed according to a mass ratio of 1:1.5, and then anhydrous ethanol is added to wet and grind for 30 minutes to obtain a mixture, and the mixed powder is added to deionized water to obtain a mixed solution, and ammonia water is added to adjust the pH of the mixed solution to 5.0, and the mixed solution is ultrasonically oscillated for 30 minutes, and then homogenized by a homogenizer at a pressure of 20MPa for 30 minutes, and after the homogenization operation, it is centrifuged at a speed of 10000rpm and washed twice with deionized water, and finally vacuum dried at 120°C to obtain a zinc aluminate graphene composite material.
[0121] Comparative Example 2
[0122] Soluble aluminum salt and soluble zinc salt are mixed according to the content ratio of aluminum element to zinc element of 2:1, and dissolved in anhydrous ethanol to obtain a mixed salt solution, 2% polyethylene glycol of the total mass of the mixed salt solution is added, and stirred at high speed for 2 hours, and the temperature is raised to 80°C and stirred until the solution becomes a gel to obtain a mixed gel solution, and the mixed gel solution is dried and ground and placed in a muffle furnace for sintering at 500°C for 8 hours to obtain zinc aluminate powder. Zinc aluminate powder and graphene oxide powder are mixed according to a mass ratio of 1:1.5, and then anhydrous ethanol is added to wet and grind for 30 minutes to obtain a mixture, and the mixed powder is added to deionized water to obtain a mixed solution, and ammonia water is added to adjust the pH of the mixed solution to 6.0, and the mixed solution is ultrasonically oscillated for 30 minutes, and then homogenized by a homogenizer at a pressure of 20MPa for 30 minutes, and after the homogenization operation, it is centrifuged at a speed of 10000rpm and washed twice with deionized water, and finally vacuum dried at 120°C to obtain a zinc aluminate graphene composite material.
[0123] Comparative Example 3
[0124] Soluble aluminum salt and soluble zinc salt are mixed according to the content ratio of aluminum element to zinc element of 2:1, and dissolved in anhydrous ethanol to obtain a mixed salt solution, 2% polyethylene glycol of the total mass of the mixed salt solution is added, and stirred at high speed for 2 hours, and the temperature is raised to 80°C and stirred until the solution becomes a gel to obtain a mixed gel solution, and the mixed gel solution is dried and ground and placed in a muffle furnace for sintering at 500°C for 8 hours to obtain zinc aluminate powder. Zinc aluminate powder and graphene oxide powder are mixed according to a mass ratio of 1:1.5, and then anhydrous ethanol is added to wet and grind for 30 minutes to obtain a mixture, and the mixed powder is added to deionized water to obtain a mixed solution, and ammonia water is added to adjust the pH of the mixed solution to 7.0, and the mixed solution is ultrasonically oscillated for 30 minutes, and then homogenized by a homogenizer at a pressure of 20MPa for 30 minutes, and after the homogenization operation, it is centrifuged at a speed of 10000rpm and washed twice with deionized water, and finally vacuum dried at 120°C to obtain a zinc aluminate graphene composite material.
[0125] Comparative Example 4
[0126] Soluble cobalt salt and soluble zinc salt are mixed according to the content ratio of aluminum element to zinc element of 2:1, and dissolved in anhydrous ethanol to obtain a mixed salt solution, 3.5% polyethylene glycol of the total mass of the mixed salt solution is added, and stirred at high speed for 4 hours, and the temperature is raised to 80°C and stirred until the solution becomes a gel to obtain a mixed gel solution, and the mixed gel solution is dried and ground and placed in a muffle furnace for sintering at 700°C for 6 hours to obtain zinc aluminate powder. Zinc aluminate powder and graphene oxide powder are mixed according to a mass ratio of 1:2, and then anhydrous ethanol is added to wet and grind for 30 minutes to obtain a mixture, and the mixed powder is added to deionized water to obtain a mixed solution, and ammonia water is added to adjust the pH of the mixed solution to 8.5, and the mixed solution is ultrasonically oscillated for 30 minutes, and then homogenized by a homogenizer at a pressure of 30MPa for 45 minutes, and after the homogenization operation, it is centrifuged at a speed of 10000rpm and washed with deionized water for 3 times, and finally vacuum dried at 140°C to obtain a zinc cobaltate graphene composite material.
[0127] Comparative Example 5
[0128] Soluble manganese salt and soluble lithium salt are mixed according to the content ratio of aluminum element to zinc element of 2:1, and dissolved in anhydrous ethanol to obtain a mixed salt solution, 3.5% polyethylene glycol of the total mass of the mixed salt solution is added, and stirred at high speed for 4 hours, and the temperature is raised to 80°C and stirred until the solution becomes a gel to obtain a mixed gel solution, and the mixed gel solution is dried and ground and placed in a muffle furnace for sintering at 700°C for 6 hours to obtain zinc aluminate powder. Zinc aluminate powder and graphene oxide powder are mixed according to a mass ratio of 1:2, and then anhydrous ethanol is added to wet and grind for 30 minutes to obtain a mixture, and the mixed powder is added to deionized water to obtain a mixed solution, and ammonia water is added to adjust the pH of the mixed solution to 8.5, and the mixed solution is ultrasonically oscillated for 30 minutes, and then homogenized by a homogenizer at a pressure of 30MPa for 45 minutes, and after the homogenization operation, it is centrifuged at a speed of 10000rpm and washed with deionized water for 3 times, and finally vacuum dried at 140°C to obtain a lithium manganate graphene composite material.
[0129] Comparative Example 6
[0130] The graphene oxide powder was ground for 30 minutes, added to deionized water for dispersion, and ammonia water was added to adjust the pH of the mixture to 8.5. The mixture was ultrasonically oscillated for 30 minutes, and then homogenized by a homogenizer at a pressure of 30 MPa for 45 minutes. After the homogenization operation, it was centrifuged at a speed of 10,000 rpm and washed with deionized water for 3 times, and finally dried in vacuum at 140°C to obtain the graphene material.
[0131] The materials obtained in the above-mentioned Examples 1 to Comparative Example 6 are respectively mixed with lead powder, sulfuric acid and water to form a paste-like mixed slurry, and the paste-like mixed slurry is coated on the negative electrode alloy grid to obtain a negative electrode of a lead-acid battery, and a lead-acid battery is made.
[0132] The lead-acid battery was subjected to a charge and discharge cycle test at 0.1C. The test results are shown in Table 1.
[0133] Table 1
[0134]
[0135] It can be seen from Table 1 that:
[0136] By comparing the data of Examples 1-3 and Comparative Examples 1-3, it can be seen that in an alkaline environment of pH 8.0-9.0, the composite effect of zinc aluminate and graphene is better, so that the zinc aluminate graphene composite material can improve the battery capacity and cycle stability when applied to lead-acid batteries.
[0137] By comparing the data of Example 3 and Comparative Example 6, it can be seen that after adding zinc aluminate to modify graphene oxide, not only the cycle stability of the battery can be improved, but also the battery capacity can be improved.
[0138] By comparing the data of Example 3, Comparative Example 4 and Comparative Example 5, it can be seen that the zinc cobaltate graphene composite material has a similar effect on improving battery capacity when applied to lead-acid batteries compared with the zinc aluminate graphene composite material of the present application, but has a significant difference in improving cycle stability. When applied to lead-acid batteries, the lithium manganate graphene composite material has the best effect on improving battery capacity compared with the zinc aluminate graphene composite material of the present application, but has the worst cycle stability.
[0139] In summary, the zinc aluminate graphene composite material of the present application can simultaneously have good battery capacity and good cycle stability when used in lead-acid batteries.
[0140] Compared with the prior art, the present invention has at least the following advantages:
[0141] The preparation method of the zinc aluminate graphene composite material of the present application first prepares zinc aluminate powder. Zinc aluminate is a type of aluminate spinel oxide. When spinel oxide is used in the negative electrode of a lead-acid battery, it can increase the capacity of the battery. Secondly, zinc aluminate spinel, as an inorganic material, is difficult to be evenly dispersed in graphene oxide without adding a coupling agent. However, in an alkaline environment of pH 8.0-9.0, the reaction activity of the carboxyl functional group, hydroxyl functional group and carbonyl functional group on the surface of graphene oxide is effectively enhanced. Zinc aluminate is reacted with [AlO3] 2- The negatively charged groups establish a covalent bond with the surface of graphene oxide with a strong connection, so that zinc aluminate is evenly dispersed in the graphene oxide, so that the zinc aluminate graphene composite material has better stability in electrode material applications. Therefore, the zinc aluminate graphene composite material has better cycle stability when used in the negative electrode of lead-acid batteries.
[0142] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a zinc aluminate graphene composite material, characterized in that: The steps include: preparing zinc aluminate powder; preparing zinc aluminate graphene composite materials; The specific steps of preparing the zinc aluminate graphene composite material are as follows: The zinc aluminate powder, graphene oxide powder and anhydrous ethanol are prepared into a mixed powder; Adding the mixed powder into deionized water to obtain a mixed solution; Performing a pH adjustment operation on the mixed solution so that the pH of the mixed solution is between 8.0 and 9.0; performing ultrasonic operation on the mixed solution; Performing a homogenizing operation on the mixed solution after ultrasound; Performing a vacuum drying operation on the mixed solution after the homogenization operation to obtain the zinc aluminate-graphene composite material; Wherein, after the mixed solution is in an alkaline environment of pH 8.0-9.0, the carboxyl functional groups, hydroxyl functional groups and carbonyl functional groups on the surface of the graphene oxide are activated, and the carboxyl functional groups, hydroxyl functional groups and carbonyl functional groups on the surface of the graphene oxide are all activated with the [AlO3] 2- The zinc aluminate and the graphene oxide are combined to form a covalent bond and then are evenly dispersed in the graphene oxide.
2. The method for preparing the zinc aluminate-graphene composite material according to claim 1, characterized in that: The specific steps of preparing the zinc aluminate powder are as follows: dissolving a soluble aluminum salt and a soluble zinc salt in the anhydrous ethanol to obtain a mixed salt solution; Adding polyethylene glycol to the mixed salt solution and performing heating and stirring operations to obtain a mixed gel solution; The mixed gel solution is sintered to obtain the zinc aluminate powder.
3. The method for preparing the zinc aluminate-graphene composite material according to claim 2, characterized in that: The soluble aluminum salt is one or both of aluminum nitrate and aluminum chloride.
4. The method for preparing the zinc aluminate-graphene composite material according to claim 2, characterized in that: The soluble zinc salt is at least one of zinc nitrate, zinc acetate, zinc chloride, zinc bromide and zinc propionate.
5. The method for preparing the zinc aluminate-graphene composite material according to claim 2, characterized in that: The sintering operation temperature is 500°C-900°C.
6. The method for preparing the zinc aluminate-graphene composite material according to claim 5, characterized in that: The sintering operation time is 5h-8h.
7. The method for preparing the zinc aluminate-graphene composite material according to claim 1, characterized in that: The pressure of the homogenization operation is 20MPa-40MPa.
8. The method for preparing the zinc aluminate-graphene composite material according to claim 7, characterized in that: The homogenization operation time is 30min-60min.
9. The method for preparing the zinc aluminate-graphene composite material according to claim 1, characterized in that: The vacuum drying temperature is 120°C-160°C.
10. A lead-acid battery negative electrode, characterized in that: The steps include: Providing the zinc aluminate graphene composite material prepared by the preparation method of the zinc aluminate graphene composite material according to any one of claims 1 to 9; The zinc aluminate graphene composite material, lead powder, sulfuric acid and water are mixed into a paste-like mixed slurry; The paste-like mixed slurry is coated on a negative electrode alloy grid to obtain the lead-acid battery negative electrode.
Citation Information
Patent Citations
Zinc-base complex oxide / graphene composite material, and preparation method and application thereof
CN102760873A
Preparation method of graphene / zinc-aluminium oxide composite material and application of composite material in super capacitor
CN103107023A